1966
DOI: 10.4098/at.arch.66-1
|View full text |Cite
|
Sign up to set email alerts
|

Biometrische und zoogeographische Untersuchungen der Gattung Apodemus (Kaup, 1829) in der Sozialistischen Republik Rumänien

Abstract: A n etw a 500 E xem p laren der G attung Apodemus w u rd en b iom etrisch e 'S tu d ien vorgen om m en so w ie der r ela tiv e W ach stu m srh yth m u s und die B esied lu n g v ersch ied en er B iotop e v erfolgt. Es w u rd e fe s tg e ste llt dass in der R u m än isch en V olk srep u b lik vier Apodem us-Arten Vorkommen: /1. sylvaticus, A. tauricus, A. microps, und A. agrarius. A u f G rund der V ariabilität der u n tersu ch ten M erkm ale w u rd e fe stg e se tz t d ass diese A rten durch N o m in at-U n te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…It should be emphasized that within Wrocław populations so far I have not observed individuals with characters resembling to the both species. The above observations have been confirmed by Hamar et al (1966) and S t e i n e r (1968). When comparing the ranges of variability of taxonomically important dimensions (hind foot, tail, Cb.-length) obtained for long tailed field mice of the age-group IV-V with the data quoted by Kowalski (1964) for A. tauricus no overlaping were found.…”
Section: Taxonomical Remarkssupporting
confidence: 63%
See 3 more Smart Citations
“…It should be emphasized that within Wrocław populations so far I have not observed individuals with characters resembling to the both species. The above observations have been confirmed by Hamar et al (1966) and S t e i n e r (1968). When comparing the ranges of variability of taxonomically important dimensions (hind foot, tail, Cb.-length) obtained for long tailed field mice of the age-group IV-V with the data quoted by Kowalski (1964) for A. tauricus no overlaping were found.…”
Section: Taxonomical Remarkssupporting
confidence: 63%
“…The maximum difference in the body length is observed in age-group IV-V, it amounts to 5 mm being the greatest known so far. It appears that most frequently it amounted to 1-2 mm (Felt en, 1952; Hamar et al, 1966), the value ranging within 4 mm has been only found by Saint Girons (1966) for A. s. dichrurus R afinesque, 1814. Results obtained by the same authoress from the environments of Paris prove that it is not a rule, since within this population she did not find any difference in the body length between the males and females.…”
Section: Sexual Dimorphismmentioning
confidence: 92%
See 2 more Smart Citations
“…A. flavicollis is a typ i cal for est-dwell ing ro dent pre ferring hab i tats with well de vel oped can opy cover (Marsh and Har ris 2000) while A. sylvaticus oc cu pies a broader spec trum of hab i tats, from early successional stages to park-like for est, avoid ing only con tin u ous for est stands (Hamar et al 1966, Steiner 1968.Re cently, the sys tem at ics and phylogenetics of the ge nus Apodemus have been widely discussed (eg Filippucci et alques tions, es pe cially the phylo gen etic re la tion -[15] Acta Theriologica 51 (1): 15-27, 2006. PL ISSN 0001-7051 Morphometric study of two spe cies of wood mice Apodemus sylvaticus and A. flavicollis (Rodentia: Muridae): tra di tional and geo met ric morphometric ap proach Lenka BARÈIOVÁ and Miloš MACHOLÁN Barèiová L. and Macholán M. 2006.…”
mentioning
confidence: 99%